The Antimicrobial Susceptibility Of Salmonella And Shigella Strains Isoiated From Fecal Specimens Of Patients With Diarrhear (Annals of Medical Research, 2021)
None
Keywords: s : Salmonella, Shigella, diarrhea, antibiotic resistance